2019
DOI: 10.1182/bloodadvances.2019000650
|View full text |Cite
|
Sign up to set email alerts
|

Induction of activated T follicular helper cells is critical for anti-FVIII inhibitor development in hemophilia A mice

Abstract: Key Points Anti-FVIII inhibitory antibody development is TFH-cell dependent. FVIII restimulation can specifically induce FVIII-primed TFH-cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…In a subsequent study, they identified an immunodominant CD4 + T-cell epitope recognized by these mice (80). The recent demonstration of expanded CD4 + T-follicular helper cells in spleens of FVIII-deficient mice with an inhibitor response has confirmed the expected essential role of this T-cell subset in providing B-cell help (43). Murine studies have also demonstrated an essential role for activated T cells in the memory B-cell response to FVIII, and the requirement for direct T-cell contact in order to re-stimulate these cells (81).…”
Section: Cd4 + T-cell Response To Fviiimentioning
confidence: 85%
See 1 more Smart Citation
“…In a subsequent study, they identified an immunodominant CD4 + T-cell epitope recognized by these mice (80). The recent demonstration of expanded CD4 + T-follicular helper cells in spleens of FVIII-deficient mice with an inhibitor response has confirmed the expected essential role of this T-cell subset in providing B-cell help (43). Murine studies have also demonstrated an essential role for activated T cells in the memory B-cell response to FVIII, and the requirement for direct T-cell contact in order to re-stimulate these cells (81).…”
Section: Cd4 + T-cell Response To Fviiimentioning
confidence: 85%
“…T follicular helper cells within germinal centers both select FVIII-specific B cells and drive affinity maturation and class-switching of their B-cell receptors, ultimately generating plasma cells that secrete high-affinity antibodies. Indeed, FVIII-deficient mice showed increased germinal center formation, proliferation of splenic Tfollicular helper cells in vitro, and accumulation of T-follicular CD4 + T cells in the spleen following FVIII immunization (43).…”
Section: Fviii Uptake Processing and Presentationmentioning
confidence: 99%
“…Finally, several studies in recent years have highlighted the important involvement of the cells in the marginal zone of the spleen in early FVIII uptake and in the development of inhibitors in mice, including splenic follicular T cells, marginal zone B cells, marginal zone macrophages, and marginal zone metallophilic macrophages (26,45,111,112). Despite this, the mechanisms of interaction between these cells in the induction of immune responses or tolerance to FVIII have yet to be described.…”
Section: Discussionmentioning
confidence: 99%
“…This observation established that CD4 + T cells play a critical role in maintaining established inhibitor responses, as well as providing initial Teffector help. Subsequent studies of both human blood samples and HA mouse models have further characterized CD4 + Tcell responses to FVIII (10,15,(30)(31)(32)(33)(34)(35). The possible roles of additional leukocyte subsets, and of inflamed endothelium, etc.…”
Section: Discussionmentioning
confidence: 99%